Effect of the curcuma plus® syrup on the pharmacokinetics of rifampicin in rats - Wahyono, Djoko; Hakim, Arief Rahman; ., Purwantiningsih (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2007)
The research was aimed to observe the effect of Curcuma plus® syrup on rifampicin pharmacokinetics in rats.The study of interaction Curcuma plus® syrup with rifampicin pharmacokinetics was conducted employing a completely randomized design using male Sprague Dawley rats which were divided into 3 groups (5 rats for each group). The groups were given a single oral rifampicin dose of 50 mg/kg BW as a control group and were confered single oral Curcuma plus syrup 2.7 mL/kg BW one hour before rifampicin and daily dose for 7 days, then is given rifampicin after that. Serial blood samples (0,2 mL) were withdrawn at various interval via the vein for HPLC analysis of unchanged rifampicin in blood. The concentration of rifampicin was determined based on a standard curve, and from the concentration to time data was determined rifampicin pharmacokinetic parameters (Cmaks, tmaks, AUC0-∼, Vd/F, t1/2, ClT dan K).The results indicated that Curcuma plus® syrup single dose 2.7 mL/kg BW one hour before rifampicin could increased rifampicin volume of distribution by 225.80% (P<0.05) and caused decreased Cmaks 72.81% and AUC0-inf 63.93% (P<0.05), while daily dose Curcuma plus® syrup for 7 days could rise rifampicin total clearance 225.60% (P<0.05) and caused decrease by 76.94% of AUC0-inf (P<0.05).Key words : pharmacokinetics, Curcuma plus® syrup, rifampicin